A prática da psicoterapia infantil a partir do referencial teórico do psicodrama, gestalt terapia e abordagem centrada na pessoa, sob as óticas de Bermúdez, Ferrari, Oaklander e Axline. - Costa, Maria Ivone Marchi (2003)
The present study has as the general objective to investigate with child psychotherapists of different theoretical approaches (Psychodrama, Gestalt and Client Centered therapy), how the clinical practice is being experienced. To do so, 6 (six) child psychotherapists, having a professional experience ranging from 10 (ten)to 30 (thirty) years, being 2 from each approach were interviewed. The interview was semi-directed and comprised the following dimensions: feelings experienced as a child psychotherapist, obstacles faced, used resources, necessities felt, evaluation of the speciality and a last question for additional information. The interviews were conducted individually and were taped and transcribed. After reading the answers of the above quoted dimensions, we can conclude that there were no differences in the responses given by the participants related to the speciality in which they work. In a general way we can say that: 1) The feelings experienced were of valuing the work with children due to its preventive character, in addition to that, it is gratifying and nice because it favors the person growth, though, at the same time the therapists feel the frustration, solitude and impotence, especially when the parents do not cooperate; 2) The obstacles faced reter to the difficulty of getting an alliance with the parents, the small number of professionals working in this area and the lack of research and related literature; 3) The used resources passed by the social network of the child (parents, relatives, friends), and regarding the technical resources, structured and non structured toys, tests and several techniques were used; 4) The necessities felt include the constant search for updating, revision through supervisions and exchange of experience with other professionals, as well as, congresses and courses; 5) The evaluation they have on the area is that, it is more difficult because it requires physical effort of the professional, the understanding of the child's language, not only verbal but also non verbal, and the cultural issue that everything that refers to children is does not receive the same value. Browsing through the several authors in whom the studies were based on, we found in the social/narrative constructionist approach a distinguished ethical position in the therapeutic practice with the children and their families. We also hold the position that the difficulties are minimized and the results more effective when the child and the family work together, either with family therapy, or brief family meetings